2004
DOI: 10.1002/ls.3010160203
|View full text |Cite
|
Sign up to set email alerts
|

Soot characterisation and diesel engine wear

Abstract: The hardness of various types of soot produced by heavy‐ and light‐duty diesel engines of European, Japanese, and North American designs was measured by low‐loss electron energy‐loss spectroscopy (EELS). No clear general trend can be established that shows heavy‐duty diesel engine soot is necessarily harder than light‐duty diesel engine soot. The variation in hardness among individual soot particles produced by the same diesel engine can be as large as differences between the hardest soot particles produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Carragher has suggested that carbon black is very soft, with hardness of ca 1 on the Mohs scale [35]. However Jao et al [26] and Yamamoto and co-workers [36] suggest much higher hardness values for soot of between 8 and 10 GPa using quite different measurement methods. Based on this Jao proposed that soot promotes wear by abrading steel surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carragher has suggested that carbon black is very soft, with hardness of ca 1 on the Mohs scale [35]. However Jao et al [26] and Yamamoto and co-workers [36] suggest much higher hardness values for soot of between 8 and 10 GPa using quite different measurement methods. Based on this Jao proposed that soot promotes wear by abrading steel surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…However Bardasz et al concluded that soot aggregates were responsible for abrasion [13]. Jao [26] showed that soot particles were sufficiently hard to abrade metal diesel engine parts. The wear scars caused by soot particles were found to contain grooves equivalent to the carbon primary particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Carraher [19] reported that CB is very soft with a hardness of ca 1 on the Mohs scale. However, Jao [20], using a different measurement method, suggested a higher value between 8 and 10 GPa.…”
Section: Methodsmentioning
confidence: 96%
“…Mogul L is a low-structure CB; it was chosen because it had an oxidised surface to facilitate dispersion and a mean particle diameter size of 24 nm, which is comparable to primary particle sizes observed for diesel soots. 7,20,21 The CB was ultrasonically dispersed in the oils using the Vibracell (Sonics & Materials, Inc., Newtown, CT, USA) at 20 kHz and 33 W for 5 min. The dispersions appeared stable over weeks.…”
Section: Oil Samplesmentioning
confidence: 99%